2012
DOI: 10.1038/bjc.2012.273
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of metastasis in women with metachronous contralateral breast cancer

Abstract: Background:The understanding of metastatic patterns after metachronous contralateral breast cancer (CBC) may help determine the biological nature of CBC.Methods:A cohort of 8478 women with breast cancer treated at Guy's and St Thomas' NHS Foundation Trust between 1975 and 2006 were studied. Organ-specific 5-year cumulative incidence and incidence rate ratios were assessed for women diagnosed with unilateral breast cancer (UBC), CBC within 5 years and CBC more than 5 years of the initial diagnosis.Results:Women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 7 publications
1
17
0
Order By: Relevance
“…Some studies have suggested that CBCs that develop within a short time interval may actually represent a form of metastatic disease. 28 More studies are needed to determine how CBC affects survival outcomes.…”
Section: Article In Pressmentioning
confidence: 99%
“…Some studies have suggested that CBCs that develop within a short time interval may actually represent a form of metastatic disease. 28 More studies are needed to determine how CBC affects survival outcomes.…”
Section: Article In Pressmentioning
confidence: 99%
“…The WHO Classification of Tumours of the Breast adopts this definition, which is used frequently in studies (Alkner et al 2011;Hartman et al 2007;Sandberg et al 2012b;Schmid et al 2011), but also mentions the benefit of a longer time interval for epidemiological [10] assessments. Many studies favour a longer cut-off time to distinguish bilateral breast cancers (Bernstein et al 2003;Londero et al 2014;Nichols et al 2011;Rubino et al 2010;Schaapveld et al 2008;Verkooijen et al 2007;Vichapat et al 2011a;Vichapat et al 2012;Vichapat et al 2011b;Yerushalmi et al 2009). As there is no consensus concerning these definitions, we conducted further analyses with different cut-off times.…”
Section: Discussionmentioning
confidence: 99%
“…Information on distant spread at diagnosis would allow for better comparison with other studies, as stage IV index tumours are generally excluded. Whether CBC should be looked at as distant spread or new primary is still open to debate (Rubino et al 2010;Vichapat et al 2012;Yerushalmi et al 2009). Complete data on tumour characteristics and therapies is not available for our All data were used anonymously in this analysis and no approval from the ethical committee of the canton of Zurich was necessary.…”
Section: Discussionmentioning
confidence: 99%
“…This view is supported by studies showing frequent discrepancies in conventional histopathologic features such as histologic type, grade or estrogen receptor status between the two primaries, although assignment of histologic grade may vary among pathologists . However, a substantial body of evidence suggests that bilateral metachronous breast cancer is associated with poor prognostic features of the initial cancer . In particular, studies have shown that patients with bilateral cancer more frequently present with advanced disease than those presenting with unilateral cancer .…”
Section: Introductionmentioning
confidence: 98%
“…3 However, a substantial body of evidence suggests that bilateral metachronous breast cancer is associated with poor prognostic features of the initial cancer. [4][5][6][7][8] In particular, studies have shown that patients with bilateral cancer more frequently present with advanced disease than those presenting with unilateral cancer. 9 These findings suggest that some CBCs may represent first site metastases.…”
Section: Introductionmentioning
confidence: 99%